ASEAN ECONOMIC TRANSFORMATION: THE ROLE OF FOREIGN INVESTMENT, HUMAN DEVELOPMENT, AND INFLATION STABILITY IN ECONOMIC GROWTH - Harahap, Siska Permata Sari; Siregar, Suci Wulandari; Harahap, Salwa Hayati; Baihaqi, Muhammad Iqbal (Accounting Department, Politeknik Negeri Bandung, 2025)
Economic growth in the ASEAN region faces complex dynamics influenced by Foreign Direct Investment or (FDI), Human Development Index (HDI), and also Inflation. The aim of this examination and research is to analyze the simultaneous influence of these three variables on economic growth in ASEAN in the 2016-2023 period using the panel data regression method. The results show that FDI has a negative and insignificant impact, indicating that the utilization of foreign investment has not been maximized and has resulted in limited infrastructure and low levels of technology uptake in various ASEAN countries. Furthermore, HDI also provides a negative and insignificant influence, indicating that the quality of Human Resource (HR) has not provided a maximum increase in economic productivity. Meanwhile, inflation has a negative but insignificant effect, consistent with the theory that uncontrolled inflation can create macroeconomic instability and reduce purchasing power.